Construction of a training curriculum system for elderly care of social workers based on post competency (基于岗位胜任力的社会工作者老年照护培训课程体系构建) - LI Xiaohua (李小花); GONG Shaohua (弓少华); GUO Hong (郭红); LIU Yu (刘宇) (中西医结合护理)
Objective To construct a training curriculum system for elderly care of social workers based on post competency. Methods On the basis of literature review and current situation investigation, the training curriculum system of elderly care for social workers was preliminarily developed, and two rounds of letter consultation were conducted on experts by Delphi method. Results The effective recovery rates of the two rounds of expert consultation questionnaires were 100% and 93. 75%, respectively, the expert authority coefficients were 0. 81 and 0. 86, and the coordination coefficients were 0. 303 and 0. 503, respectively. A training curriculum system for the elderly care of social workers, including 6 first-level indicators and 30 second-level indicators, was preliminarily constructed. Conclusion The expert consultation of the elderly care training curriculum system for social workers tends to be consistent, and experts are highly motivated and authoritative, which can provide references for the pre-employment and on-job training courses for elderly social workers, but further empirical research is needed to test and improve. (目的 构建基于岗位胜任力的社会工作者老年照护培训课程体系。方法 在文献回顾和现状调查的基础上, 初步拟定社会工作者老年照护培训课程体系, 运用德尔菲法对专家进行两轮函询。结果 两轮专家咨询问卷的有效回收率分别为100. 00% 和93. 75%, 专家权威系数分别为0. 81和0. 86, 协调系数分别为0. 303、0. 503, 初步构建了包括 6个一级指标、30个二级指标的社会工作者老年照护培训课程体系。结论 构建的社会工作者老年照护培训课程体系专家咨询意见趋于一致, 专家的积极性和权威性较高, 能够为老年社会工作者入职前和在岗培训课程提供参考, 但需要进一步的实证研究进行检验和完善。)